2017
DOI: 10.1177/1010428317715643
|View full text |Cite
|
Sign up to set email alerts
|

Tim-3 as a diagnostic and prognostic biomarker of osteosarcoma

Abstract: Osteosarcoma is the most frequent primary bone tumor that affects adolescents and children. However, diagnostic and prognostic biomarkers for osteosarcoma remain lacking. (Tim-3) T-cell immunoglobulin domain and mucin domain-3, which negatively regulates T cell helper (Th1) cells and affects cytokine expression, has attracted increasing attention due to its critical role in regulating both adaptive and innate immune cells. In this study, we evaluated serum soluble Tim-3 level in osteosarcoma patients to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Instead, it has been proposed that soluble TIM3 is a result of metalloproteinase-dependent cleavage that facilitates its shedding from the cell surface 19 . Since elevated plasma levels of TIM3 have been reported in patients with graft-versus-host disease 20 and in patients with osteosarcoma 21 , soluble TIM3 may serve as a biomarker for these maladies. Elevated plasma levels of TIM3 also appear to correlate with enhanced viral load in patients with HIV infection 18 .…”
Section: Checkpoint Receptorsmentioning
confidence: 99%
“…Instead, it has been proposed that soluble TIM3 is a result of metalloproteinase-dependent cleavage that facilitates its shedding from the cell surface 19 . Since elevated plasma levels of TIM3 have been reported in patients with graft-versus-host disease 20 and in patients with osteosarcoma 21 , soluble TIM3 may serve as a biomarker for these maladies. Elevated plasma levels of TIM3 also appear to correlate with enhanced viral load in patients with HIV infection 18 .…”
Section: Checkpoint Receptorsmentioning
confidence: 99%
“…These soluble-CRs can act as agonists or antagonistic molecular decoys and can orchestrate host immunity distally, performing paracrine tasks similar to stimulatory or inhibitory cytokines. Systemic concentrations of several soluble-CRs rise during inflammation, autoimmunity (Jung et al, 2003;Lahat et al, 2003;Ip et al, 2005Ip et al, , 2006Cao et al, 2012;Delmastro et al, 2012;Chiba et al, 2017;Lin et al, 2018), infectious diseases (Cao et al, 2011;Clayton et al, 2015;Ren et al, 2015;Zilber et al, 2019), and cancer (Prigent et al, 1999;Triebel et al, 2006;Hock et al, 2009;Heo et al, 2012;Ge et al, 2017;Silva et al, 2017;He et al, 2018;Li N. et al, 2018) often mirroring immune dysfunction, disease progression and increased mortality. Measurements of systemic soluble-CRs are useful both as potential diagnostic/prognostic biomarkers (Chen et al, 2017;Li Y. M. et al, 2018) but also to expose mechanisms underlying immunopathogenesis of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of TIM-3 expression has been observed on exhausted CD8 + T cells (39,40). In certain tumors, such as lung cancer, lymphomas and breast cancer, higher quantities of Tim-3 + CD8 + T cells were associated with poor disease outcomes (41)(42)(43)(44)(45). Ge et al (42) reported that Tim-3 + CD4 + T and CD8 + T cells may serve as novel diagnostic and prognostic biomarkers of OS.…”
Section: Discussionmentioning
confidence: 99%
“…In certain tumors, such as lung cancer, lymphomas and breast cancer, higher quantities of Tim-3 + CD8 + T cells were associated with poor disease outcomes (41)(42)(43)(44)(45). Ge et al (42) reported that Tim-3 + CD4 + T and CD8 + T cells may serve as novel diagnostic and prognostic biomarkers of OS. However, to the best of our knowledge, the number of Tim-3 + CD8 + T cells in peripheral blood specimens from patients with STS has not been previously investigated, with respect to disease progression and patient survival.…”
Section: Discussionmentioning
confidence: 99%